SEISMIC RISK ANALYSIS OF PUBLIC BUILDINGS WITH BASE ISOLATION USING INCREMENTAL DYNAMIC ANALYSIS (IDA) METHOD - Pramesti C. W. D; Sangadji S; Saifullah H. A (Jurnal Geosaintek, 2026)
Earthquake can induce dynamic vibrations in building structures, which may compromise their durability and pose significant challenges to structural integrity, thereby necessitating effective protective measures. In this study, seismic base isolation was applied to reinforced concrete building structures. Base isolation is one of the effective techniques in protecting structures exposed to earthquake stimuli. In assessing the effect of the isolation system, a comparative analysis is conducted between 7-story reinforced concrete buildings without seismic protection and those equipped with Lead Rubber Bearing (LRB). In analyzing the dynamic response of the structure, Incremental Dynamic Analysis (IDA) was performed through numerical simulations using nine selected earthquake acceleration records with the aid of the Seismostruct application. The analysis results indicate that the structural resistance of the building significantly affects the seismic forces, particularly when comparing the existing structure with the base-isolated model. The structure quipped with a base isolation system demonstrates a more controlled behavior and a substantially reduced displacement response compared to the non-isolated building. In addition, the fragility curves of the two buildings show clear differences. According to the HAZUS-MH MR5 guidelines, the base-isolated structure remains below the significant damage threshold, demonstrating an overall enhancement in seismic performances.